Pharmacological treatment - Schmidt, Dieter (Henry Stewart Talks, 2011)
Current drug treatment of epilepsy, Four major questions, How and when to start AEDs?, Which AED?, How to optimize the benefit/risk balance of pharmacological treatment for your patient?, How and when to stop AEDs?, What are the unmet need of current treatment and what to do about it?